Influence of applied nitrogen on productivity, profitability and resource-use efficiency in winter barley (Hordeum vulgare) under semi–arid conditions of Afghanistan - KOHISTANI, ABDUL WAHED; CHOUDHARY, ANIL K (The Indian Journal of Agricultural Sciences, 2019)
Barley (Hordeum vulgare L.) is the major cereal in majority of global drylands and thus, vital for the livelihoods of resource-poor farmers of such harsh agro-ecologies (Rana et al. 2014). Barley is such an annual cereal crop grown in environments ranging from the deserts of the Middle East to the higher elevation of Himalayas (Hayes et al. 2003). Barley has the ability to replace the wheat as the dominant crop due to its tolerance to drought and salinity in dryland areas (Rana et al. 2014), thus, it is a potential alternate cereal crop for wheat under changing climate scenario. Barley is more productive under adverse environments than other cereals. That’s why; the barley is cultivated in all the provinces of Afghanistan in a wide range of agro-climatic conditions. The major barley growing provinces of Afghanistan are Takhar, Balkh, Faryab, Jawzjan and Ghazni (Afghanistan Statistical Yearbook 2016â€“17). According to Afghanistan Statistical Yearbook (2016â€“2017), the area, production and productivity of barley is drastically reducing in Afghanistan year after year due to poor productivity of the crop. At present, the area under barley cultivation is 219208 ha with the production of 301856 metric tons and average productivity of 1.38 t ha-1 (Afghanistan Statistical Yearbook 2016â€“17). The major constraints for low barley productivity in the nation are poor nitrogen (N) management and rainfed agro-ecologies (Omran et al. 2018). Since, the development of irrigation infrastructure needs huge investments in the nation, however, the precise N management strategy may still abridge the production gaps upto some extend and may result in large economic benefits to Afghan farmers. The rate of uptake and partition of N is largely determined by supply and demand during various stages of plant growth. Soil N supply, for example, must be high at tillering, stem elongation, booting, heading and grain filling requiring a greater amount for the development and growth of its reproductive organs and for an enhanced and high accumulation of proteins in the kernel (Choudhary et al. 2010). Moreover, nitrogen is considered as one of the most important factors affecting crop morphology. Thus, keeping in view above facts an investigation was undertaken by in winter barley.